Pengaruh Supervisi Keperawatan Terhadap Persepsi Penerapan Patient Safety Dan Pendokumentasian Asuhan Keperawatan - Ardicho Irfantian; Fitri Arofiati (Jurnal Admmirasi, 2018)
The data from BPPS Kemenkes RI 2017 showed that the percentage of nurse was 49% from the whole paramedic (Doctor, specialist doctor, midwife, pharmacy, dentist) in a Health Service Facility. A good nurse would create a good health service. One of the quality indicators was the application of patient safety and the completeness of nursing care documentation. It was essential to hold nursing supervision in order to control and maintain this quality. Investigating the correlation between the implementation of nursing supervision and the perception of the patient safety application also the nursing care documentation in RSUD Kota Yogyakarta. Quantitative research using descriptive approach. The instrument was questionnaire that adapted and modified from patient safety standard as well as some previous research. The data were taken through questionnaire that allotted to nurses during December 2017 in RSUD Kota Yogyakarta. 50% of respondents stated that nursing supervision planning were good, 60% stated that supervision implementation was not quite good, and 51% stated that supervision evaluation was good. The good supervision affects good performance. Nursing supervision doesn't influence to the perception of patient safety application and nursing care documentation in RSUD Yogyakarta, but the most influential nursing supervision variable on the perception of patient safety application is nursing supervision implementation, and there is a negative influence on the variable of nursing supervision planning on nursing care documentation in RSUD Yogyakarta.